2017
DOI: 10.1021/acs.biochem.7b00335
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Conversion of Flavin Adenine Dinucleotide (FAD) to 8-Formyl FAD in Formate Oxidase Results in a Modified Cofactor with Enhanced Catalytic Properties

Abstract: Flavins, including flavin adenine dinucleotide (FAD), are fundamental catalytic cofactors that are responsible for the redox functionality of a diverse set of proteins. Alternatively, modified flavin analogues are rarely found in nature as their incorporation typically results in inactivation of flavoproteins, thus leading to the disruption of important cellular pathways. Here, we report that the fungal flavoenzyme formate oxidase (FOX) catalyzes the slow conversion of noncovalently bound FAD to 8-formyl FAD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 29 publications
6
41
0
Order By: Relevance
“…We propose that the oxidation of the 8α-methyl group is initiated by proton abstraction, as proposed previously ( 16 18 ), leading to the formation of a negative charge at the N(1)–C(2)=O locus of the isoalloxazine ring. After addition of water, the reduced intermediate is oxidized to yield the 8α-hydroxymethylene intermediate, which is again subject to proton abstraction at the 8α-group with the resulting enol tautomerizing to the reduced 8f-FAD.…”
Section: Discussionsupporting
confidence: 65%
“…We propose that the oxidation of the 8α-methyl group is initiated by proton abstraction, as proposed previously ( 16 18 ), leading to the formation of a negative charge at the N(1)–C(2)=O locus of the isoalloxazine ring. After addition of water, the reduced intermediate is oxidized to yield the 8α-hydroxymethylene intermediate, which is again subject to proton abstraction at the 8α-group with the resulting enol tautomerizing to the reduced 8f-FAD.…”
Section: Discussionsupporting
confidence: 65%
“…Amplitudes were fit to a single exponential decay in time. A shoulder around 520 nm persisted in the absorbance spectrum collected after heat-denaturation and the short-wavelength maximum was shifted to 360 nm vs 375 for authentic FAD consistent with possible modification of some of the flavin (48,114). (B) Near-UV CD spectra of the same sample as described in (A) with inset showing time course of tertiary structural change based on molar ellipticity at 280 nm.…”
Section: Data Availabilitymentioning
confidence: 77%
“…hETF is oxidized at the 8a-position to yield 8-formyl-FAD upon incubation under slightly alkaline conditions [17]. Interestingly, this reaction is promoted by bTyr16 in hETF [17,28,29] and thus we hypothesized that yETF may be resistant toward oxidation of the FAD cofactor. To test our hypothesis, we transferred purified yETF to 50 mM HEPES pH 8.5 containing 1 mM DTT and incubated the sample at 25°C for 24 h. After denaturation of the protein, the free cofactor was analyzed on HPLC-DAD, which indeed revealed no 8-formyl modification of the flavin cofactor.…”
Section: Comparison Of the Yeast Etf To The Human Homologmentioning
confidence: 97%
“…The only obvious difference found in the active site of the model is the change of Tyr16 in hETF to Phe19 in yETF in the b-subunit (Fig. Interestingly, this reaction is promoted by bTyr16 in hETF [17,28,29] and thus we hypothesized that yETF may be resistant toward oxidation of the FAD cofactor. Recently, we have shown that the FAD cofactor of with 50 mM HEPES pH 7 + 1 mM DTT (black line) and denatured using 2% SDS (red line) were recorded between 300 and 800 nm at 25°C.…”
Section: Comparison Of the Yeast Etf To The Human Homologmentioning
confidence: 98%